Rekomendasi Diet Bagi Penderita Penyakit Diabetes Menggunakan Metode K-Nearest Neighbor - Fitri Wulandari; Fitri Insani; Nurismi Dhuha (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Gestational Diabetes Mellitus Diabetes is the kind experienced by women during pregnancy. Theproblems that arise in the treatment is to calculate the dietary levels of patients according to the exactneeds based on nutritional status and physical activity of patients. Hence made a decision support systemfor dietary recommendations for patients with this disease to facilitate the patient's nutrition and caloriecounting is right, and combine various types of foods that are equivalent to the level of patient's diet. Thisapplication uses the K-Nearest Neighbor method to calculate the appropriate dietary recommendationsand the combination diet for patients with this disease. Input data obtained from medical records ofpatients with Gestational Diabetes Mellitus and diets of data that comes with the amount of calories,calculation is then performed by finding the shortest distance between the data before the data that will betested. From the calculation result of a food menu and menu recommendations replacement ascombinations of foods by the number of calories the patient.Keywords: Diabetes Mellitus Gestasional, K-Nearest Neighbor, Decision Support System